2019
DOI: 10.1017/s1478951519000208
|View full text |Cite
|
Sign up to set email alerts
|

Brief emotional screening in oncology: Specificity and sensitivity of the emotion thermometers in the Portuguese cancer population

Abstract: ObjectiveThis study aimed to determine the cutoff and the specificity and sensitivity of the Emotion Thermometers (ET) in a Portuguese sample of cancer patients.MethodA total of 147 patients (mean age = 49.2; SD = 12.6) completed the ET, the Brief Symptom Inventory (BSI), and the Subjective Experiences of Illness Suffering Inventory. Data were collected in a cancer support institution and in a major hospital in the North of Portugal.ResultThe optimal cutoff for the Anxiety Thermometer was 5v6 (until 5 and 6 or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Overall, the results showed, as expected, that most of the patients experienced high levels of distress, with 87% of patients being above the cut-off (≥5) proposed by Teixeira et al [23]. Thus, it confirms the results of previous studies showing that cancer patients tend to experience a wide range of negative outcomes [2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Overall, the results showed, as expected, that most of the patients experienced high levels of distress, with 87% of patients being above the cut-off (≥5) proposed by Teixeira et al [23]. Thus, it confirms the results of previous studies showing that cancer patients tend to experience a wide range of negative outcomes [2][3][4][5][6].…”
Section: Discussionsupporting
confidence: 89%
“…In a recent review concerning the use of ETs among individuals diagnosed with cancer, Harju et al stated that overall ETs are a sensitive tool to screen for distress, as found by five validation and two exploratory studies, that recommended a cut-off equal to or greater than four [22]. In Portugal, the ETs were validated by Teixeira et al using a sample of 147 cancer patients [23]. The authors found that the ETs have excellent discrimination and identified the optimal cut-off values for each ET.…”
Section: Introductionmentioning
confidence: 99%
“…Depression was measured by the Patient Health Questionnaire-9 (PHQ-9), using a 9-item 4-point Likert scale, with higher total scores indicating a higher level of depression symptoms; a cut-off score of 7 indicated high risk of clinical depression 30 , 31 . Hostility was measured by hostility subscale of the Brief Symptom Inventory (BSI), which consists of five items with rating from 0 (not at all) to 4 (extremely);a cut-off scores of 4 indicated higher risk of hostility 32 , 33 . COVID-19-related PTSD was measured by the Impact of Events Scale-Revised (IES-R), which is a 22-item 5-point Likert scale; higher total scores indicate severe PTSD symptoms, with a cut-off score of 33 to recommended PTSD diagnosis 34 .…”
Section: Methodsmentioning
confidence: 99%
“…The “Anger Thermometer” was able to detect cases of significant distress (cut‐off score of 4) that were not identified by using the conventional Distress Thermometer (DT) only. Again, “caseness” of anger on the Anger‐ET was found in 15% of 149 breast cancer patients 31 and in 24% in a large sample of over 2,000 cancer patients, 32 in 18% of 158 long survivors of cancer by using the Anger/Hostility dimension of the Profile of Mood sates (POMS), 33 and in 28% out of 147 cancer patients by using the BSI‐HOS subscale 34 . This suggests that carefully exploring these dimensions among the several emotional reactions to cancer in structured program for early screening in cancer care is necessary and clinically useful 35,36 …”
Section: Introductionmentioning
confidence: 99%